Factors associated with high HIV-related stigma among commuter populations in Johannesburg, South Africa - Peter S. Nyasulu; Ndumiso Tshuma; Lovemore N. Sigwadhi; Juliet Nyasulu; Modupe Ogunrombi; Lucy Chimoyi (Taylor & Francis Group, 2021)
Stigma remains an important barrier to seeking and staying in care among individuals infected with Human Immunodeficiency Virus (HIV). Despite continued widespread information, education and communication campaigns to raise awareness about the infection. The aim of the study was to identify factors related to HIV stigma among a commuter population in the inner-city Johannesburg. A self-administered closed-ended questionnaire was loaded onto personal tablet computers during a community outreach campaign. The outcome was measured by asking the respondents to rate their perceptions of stigma as 'high or low'. About 1146 participants were enrolled in the study of which 585 (51.0%) reported high stigma levels. Overall, being married/cohabiting (Adjusted Prevalence Ratio (APR): 1.14 95%CI: 1.02-1.28), divorced (APR: 1.38 95%CI: 1.07-1.78), were associated with high levels of stigma; while being aware of HCT services (APR: 0.85 95%CI: 0.75-0.97) and employment status (APR: 0.78 95%CI: 0.71-0.87) were less likely associated with a high level of stigma. High HIV stigma still exists among those affected in our communities. Enhancement of health promotion intervention and reinforcing the benefits of knowing HIV status is essential to mitigate factors shown to influence stigma in the commuter population. Such an approach would help overcome stigma, an obstacle for expanding access to HIV testing and counselling.